The descriptive study about personality character and self-fulfillment of students in islamic boarding school - Reza Fahmi; Firman Firman; Mukhaiyar Mukhaiyar; Mudjiran Mudjiran (International Conferences on Educational, Social Sciences and Technology)
The aims of the study; (1) to describe the small and medium industry Darul Ma'rifat roomates Modern Islamic Boarding School of Islamic Boarding School Operate. (2) to describe about the character of students who manage the small and medium industry. (3) Correlation between personality character and self-fulfillment of students. Then, 172 students were the populations. But, only 120 students were a sample of the study. The Data collected by psychological scale (self-fulfillment scale), interviews and documentation of data.. The result: according To Pearson correlation the research got the coefficient correlation r count > r table (0.275> 0.211). It means rijected H0 and Ha has been recieved. So, there were correlation between small-medium industry and self-fulfillment students.